2003
DOI: 10.1177/0887403403253724
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Extralegal Determinants of Intercounty Differences in Prison Use

Abstract: Although many studies have used states' stock imprisonment rates to gauge the relative punitiveness of U.S. jurisdictions, there has been much less systematic research designed to explain the significant county-level differences in sentencing outcomes within the United States. This study focuses on the impact of new court commitments on prison use, using a 1998 national sample of court data from 172 U.S. counties to document and explain variations in use of prison as a sentencing option. Multivariate linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 32 publications
3
49
0
1
Order By: Relevance
“…Other studies reveal either no support for racial threat (Kautt, 2002;Weidner & Frase, 2003;Weidner, Frase, & Pardoe, 2004), or evidence contrary to racial threat hypotheses (Britt, 2000). Feldmeyer and Ulmer (2011) found that, though race effects varied significantly between federal courts, federal districts' percent black was unrelated to black/white disparities.…”
Section: Racial/ethnic Population Compositionmentioning
confidence: 89%
“…Other studies reveal either no support for racial threat (Kautt, 2002;Weidner & Frase, 2003;Weidner, Frase, & Pardoe, 2004), or evidence contrary to racial threat hypotheses (Britt, 2000). Feldmeyer and Ulmer (2011) found that, though race effects varied significantly between federal courts, federal districts' percent black was unrelated to black/white disparities.…”
Section: Racial/ethnic Population Compositionmentioning
confidence: 89%
“…While the full dynamics of the political process and its influence on prosecutorial decision making cannot be assessed with the current data, one aspect of this process can be assessed. Specifically, judges and prosecutors operating in more conservative jurisdictions should be influenced in such a manner that they respond more punitively as compared to those operating in more liberal jurisdictions (Taggart & Winn, 1993;Weidner & Frase, 2003). This notion is grounded in research indicating that conservative views are generally more consistent with a strong focus on punishment as compared to liberal views (see Cullen, Pratt, Miceli, & Moon, 2002).…”
Section: Prosecutorial Decision Making and The External Communitymentioning
confidence: 95%
“…support for claims that increased Republican political dominance had independent positive effects on state imprisonment rates (Stucky et al 2005, Yates & Fording 2005, Western 2006, Spelman 2009). Weidner & Frase (2003) used a different strategy. They assessed the relationship between the percentage of county voters who supported the law-and-order Bush Republican candidacy in the 1988 presidential election and the number of prison sentences in 172 counties.…”
Section: Statistical Analysesmentioning
confidence: 99%